Spatial Distribution of the Probability of Satisfying the Chill Requirements of Pistachio in Iran Using ERA5-Land Reanalysis Data - Ebrahim Asadi Oskouei; Saeedeh Kouzegaran; Mansoureh Kouhi; Hossein Hokmabadi; Mohsen Eslami (Nīvār)
The pistachio nut is native to Iran and this country has the most favorable climate for cultivating pistachio trees. Generally, there were only five main pistachio producing-provinces in Iran including Kerman, Khorasan, Yazd, and Semnan. Temperature, specifically winter chill accumulation, is generally considered to be a decisive climatic factor in flowering and fruit sets. Pistachio trees require winter chilling to overcome their dormancy and initiate fruiting. If the winter chilling requirements are not met, the pistachio tree may not achieve the best yield the following year, or may not produce any fruit at all. The main goal of this work is to calculate the chilling requirements for breaking the dormancy of four pistachio cultivars, using the CH method. ERA5-Land reanalysis data of temperature have been used to delimit the potential spatial distribution of chill accumulation for these cultivars in Iran during 1981-2021. Moreover, the probability of satisfying the chilling requirements has been mapped to delineate the appropriate zones of the country where the chilling requirements can be met. The results showed the Kalle-Ghuchi cultivar could be potentially cultivated in almost every location of Iran, except coastal and mountainous areas where the chilling requirements would not be met. If a higher probability of satisfying the chilling requirements is desired (75% of the years, the requirements of winter chilling are achieved) around 0.2, 29, 47 and 66 percent of the area of Iran are potentially suitable for Akbari, Owhadi, Ahamd-Aghaei and Kalle-Ghuchi cultivars respectively. Kalle-Ghuchi can be grown with a high probability of chilling requirement satisfaction in wide areas of Iran. This information can be used to advise pistachio farmers about which cultivars are best suited to their area and which areas of our region are the most appropriate for pastiche production.